Sex-specific impact of asthma during pregnancy on infant gut microbiota. Issue 5 (23rd November 2017) - Koleva, Petya T.; Tun, Hein M.; Konya, Theodore; Guttman, David S.; Becker, Allan B.; Mandhane, Piush J.; Turvey, Stuart E.; Subbarao, Padmaja; Sears, Malcolm R.; Scott, James A.; Kozyrskyj, Anita L.
Asthma during pregnancy is associated with retardation of fetal growth in a sex-specific manner. Lactobacilli microbes influence infant growth. This study aimed to determine whether lactobacilli and other microbes are reduced in the gut of infants born to an asthmatic mother, and whether this differs by the sex of the infant. Mother-infant pairs (N=1021) from the Canadian Healthy Infant Longitudinal Development full-term cohort were studied. The abundance of infant faecal microbiota at 3–4 months, profiled by gene sequencing, was compared between both women with and without asthma treatment during pregnancy. Infant sex, maternal ethnicity, pre-pregnancy overweight and atopy status, birth mode, breastfeeding status and intrapartum antibiotic treatment were tested as covariates. Independent of birth mode and other covariates, male, Caucasian infants born to women with prenatal asthma harboured fewer lactobacilli in the gut at 3–4 months of age. If asthmatic mothers had pre-pregnancy overweight, the abundance of Lactobacillus in males was further reduced in the infant gut, whereas the microbiota of female infants was enriched with Bacteroidaceae . Similar differences in infant gut microbial composition according to maternal prenatal asthma status were also more evident among women with food or environmental allergies. Gut lactobacilli were less abundant in male infants, but Bacteroidaceae were more abundant in female infants at 3–4 months of age, following maternal asthma during pregnancy. Gut lactobacilli are less abundant at 3–4 months in male but not female infants following maternal prenatal asthma http://ow.ly/jXnl30fU9xH